First-time versus repeat visitors’ behavior patterns: a GPS analysis - Núria Galí Espelt; José A. Donaire Benito (Boletín de la Asociación de Geógrafos Españoles)
Past research conducted on visitors' behavior has highlighted the differences between first-time and repeat visitors in urban and natural settings. To determine whether these differences also exist in a monumental city, we have studied visitor behavior in the historic city of Girona (Spain). Data from 1288 GPS tracking were recorded. Of these, 928 were first-time visitors, and the remaining 360 corresponded to repeat visitors. Findings show that there is very little difference in how first-time and repeat visitors act, compared to visitor behavior in other types of tourist destinations. Nevertheless, the results do demonstrate differences between low frequency visitors (between 1 and 4 visits) and high frequency visitors (more than 4 visits). These results suggest that sightseeing creates very homogeneous behavior pattern between first-time and repeat visitors, and highlight the need to differentiate repeat visitors according to the number of visits done in the monumental city.